In planta function of compatible solute transporters of the AtProT family - Lehmann, Silke (Journal of experimental botany, 2011)
The three proline transporters of Arabidopsis thaliana (AtProTs) transport the compatible solutes proline and glycine betaine and the stress-induced compound γ-aminobutyric acid when expressed in heterologous systems. The aim of the present study was to show transport and physiological relevance of these three AtProTs in planta. Using single, double, and triple knockout mutants and AtProT-overexpressing lines, proline content, growth on proline, transport of radiolabelled betaine, and expression of AtProT genes and enzymes of proline metabolism were analysed. AtProT2 was shown to facilitate uptake of L- and D-proline as well as [(14)C]glycine betaine in planta, indicating a role in the import of compatible solutes into the root. Toxic concentrations of L- and D-proline resulted in a drastic growth retardation of AtProT-overexpressing plants, demonstrating the need for a precise regulation of proline uptake and/or distribution. Furthermore evidence is provided that AtProT genes are highly expressed in tissues with elevated proline content--that is, pollen and leaf epidermis